Bibliometric analysis of global research trends and development prospects of Smilax glabra Roxb using CiteSpace - Shi, Wenqing; Li, Xiao; Zhao, Xin; Jiang, Jingjing; Wang, Chenxi; Fan, Guorong; Lou, Yuefen (Frontiers in Plant Science, 2025)
IntroductionSmilax glabra Roxb (SGR) is extensively utilized in the management of disorders, including hyperuricemia and gout, due to its notable pharmacological effects, and it is also the primary component in the functional food turtle jelly. Despite extensive research on SGR, no systematic statistical analysis of the literature has been conducted on it. This study provides a comprehensive bibliometric analysis of SGR, identifies the current research landscape, identifies hotspots, and performs trend analysis.MethodsAll Chinese and English literatures pertaining to SGR was gathered from Web of Science Core Collection (WoSCC), China Knowledge Network (CNKI), Wanfang database, and VIP database, subsequently de-duplicated and organized, with CiteSpace software employed for visualization and analysis of the literature.ResultsA total of 1723 articles were incorporated into the analysis, and the quantity of SGR-related publications in English persists in its upward trajectory. Sun Weifeng, Lisa Dong, and Zhang Qingfeng emerged as the principal contributors, while Beijing University of TCM and Zhejiang University of TCM established themselves as the foremost publishing organizations. Noteworthy, keywords indicative of contemporary research focal points encompassed “Chinese medicine treatment,” “gout,” “anti-inflammatory,” and “network pharmacology.”DiscussionThe investigation into SGR concentrates on pharmaceuticals and their active components, therapeutic interventions, and pharmacological mechanisms. Recently, anti-inflammatory and cyberpharmacology have emerged as prominent trends, indicating that the integration of animal studies with molecular bioinformatics to investigate the pharmacological mechanism of SGR is the main research direction in the future, while cardiovascular protection and neuroprotective effects have become significant areas of recent inquiry. Consequently, SGR is anticipated to be a functional plant for the treatment of various diseases.